The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/bem.20246
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a moderate‐intensity static magnetic field on VEGF‐A stimulated endothelial capillary tubule formation in vitro

Abstract: Effects of a moderate-intensity static magnetic field (SMF) on the early-stage development of endothelial capillary tubule formation were examined during the initial cell growth periods using co-cultured human umbilical vein endothelial cells and human diploid fibroblasts. The co-cultured cells within a well (16 mm in diameter) were exposed to SMF intensity up to 120 mT (Bmax) with the maximum spatial gradient of 21 mT/mm using a disc-shaped permanent magnet (16 mm in diameter and 2.5 mm in height) for up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 65 publications
4
40
0
1
Order By: Relevance
“…To our knowledge, this is the first study reporting a passage number-dependent but donor age-independent decline in angiogenic activity in ASC-CM. VEGF-A [34], HGF [36], and FGF-2 [35] stimulate the formation of tube-like structures in this assay system. As shown in Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…To our knowledge, this is the first study reporting a passage number-dependent but donor age-independent decline in angiogenic activity in ASC-CM. VEGF-A [34], HGF [36], and FGF-2 [35] stimulate the formation of tube-like structures in this assay system. As shown in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies demonstrated that angiogenic factors such as VEGF-A [34], FGF-2 [35], and HGF [36] promote HUVEC tube formation. We next evaluated the concentration of these angiogenic factors in ASC-CM using ELISA.…”
Section: Donor Age Affects Vegf-a Secretion By Ascsmentioning
confidence: 99%
“…Furthermore effects of moderate-intensity static magnetic field (SMF) on the VEGF-A-enhanced tubule formation investigated by Okano in 2006 reveals that SMF seems to be synergistic or additive in arteriogenesis but not in angiogenesis and it significantly promoted the VEGF-A-increased area density and length of tubules in the peripheral part of the wells, compared with the VEGF-A treatment alone. However, SMF did not induce any significant changes in the VEGF-A-increased number of bifurcations in any part of the wells [25]. Additionally it is reported that Pulsed electromagnetic fields (PEMF) had ability to increase in vitro and in vivo angiogenesis through endothelial release of FGF-2 and inducing paracrine and autocrine changes in the surrounding tissues [26].…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed electromagnetic fields were shown to induce vascular endothelial cell growth and angiogenesis through influencing the vascular endothelial growth factor (VEGF)-related pathways. 24,25 In another study, Yuan et al 26 reported induced angiogenesis and the improvement of cardiac function in a surgically-induced infarcted myocardium, after implementing a pulsed magnetic field. In this current study, although in both clinical and histopathologic investigations, there was not a remarkable difference in the rate of stromal neovascularization between the groups; the progression rate of neovascularization over a 2-week period was statistically significant in the magnetic therapy groups and was comparable with the control; such a progression, however, was not observed in the MT group; this was probably due to use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%